PENGARUH MODEL EXAMPLE NON_EXAMPLE (ENE) DAN INSIDE OUTSIDE CIRCLE (IOC) DALAM PEMBELAJARAN BERBANTUAN MEDIA AUDIOVISUAL - Muchamat Saiful (Universitas Muria Kudus, 2019)
This study aims to describe the influence of exampel non_example and inside outside circle learning models in thematic learning assisted by audiovisual media of IVSD 2 grade students Temulus, 3 Temulus and 3 Kirig Mejobo Kudus on the sub-theme 1 ethnic diversity and religion in my country in Indonesian and Science. The research method used is experimentation. The design used in experimental research using the design "pre test and post test design". This study was divided into three groups: the first group learning with the Example Non Example model assisted by audiovisual media, the second group learning with the IOC model assisted by audiovisual media, and the third group learning with conventional models (control class). The subjects in this study were all class IV in Mejobo District. The research sample was taken from 3 classes selected purposively, namely SD 2 Temulus, SD 3 Temulus, and SD 3 Kirig. The results of this study indicate that (1) There is a significant effect Example Non Example Learning Model in thematic learning assisted by audiovisual media in Class IV of Elementary School. The results of data analysis state thitung> t table (5,982> 2,056), then Ha is accepted; (2) There is a significant effect of Inside Outside Circle Learning Model in thematic learning assisted by audiovisual media of Grade IV Elementary School Students. The results of data analysis state thitung> t table (4,269> 2,074); (3) There is a difference between Example Non Example Learning Model and Inside Outside Circle Learning Model in audiovisual assisted thematic learning in Class IV Elementary School Students, but not significant. The results of data analysis state that t count> t table (3,043> 2,048), then Ha is accepted. But the significant results obtained a number of 0.348> 0.025.